2020
DOI: 10.1186/s12889-020-08619-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of global budget on expenditure, service volume, and quality of care among patients with pneumonia in a secondary hospital in China: a retrospective study

Abstract: Background: The Chinese government has begun to dampen the growth of health expenditure by implementing Global Budgets (GB). Concerns were raised about whether reductions in expenditure would lead to a deterioration of quality of care. This paper aims to evaluate the impact of GB on health expenditure, service volume and quality of care among Chinese pneumonia patients. Methods: A secondary hospital that replaced Fee-For-Service (FFS) with GB in China in 2016 was sampled. We used daily expenditure to assess he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Previous studies highlight that the single healthcare provider payment reforms occasionally result in the increase in the proportion of the OOP expenditure or other medical costs of healthcare services ( 27 , 28 ). In China, the healthcare service purchasers, such as the Healthcare Security Administration, preferred to use the single healthcare provider payments, such as the global budget or quota payments to pay for hospitals through “premium packages” ( 7 , 29 ). Additionally, the payment standards of single healthcare provider payments used in China commonly lack the detailed risk-adjustment mechanisms that generate payment standards, which cannot satisfy the practical demand of different hospitals ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies highlight that the single healthcare provider payment reforms occasionally result in the increase in the proportion of the OOP expenditure or other medical costs of healthcare services ( 27 , 28 ). In China, the healthcare service purchasers, such as the Healthcare Security Administration, preferred to use the single healthcare provider payments, such as the global budget or quota payments to pay for hospitals through “premium packages” ( 7 , 29 ). Additionally, the payment standards of single healthcare provider payments used in China commonly lack the detailed risk-adjustment mechanisms that generate payment standards, which cannot satisfy the practical demand of different hospitals ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over past decades, total health expenditure (THE) in China has rapidly increased ( 5 ). This is thought to be a result of the prolonged use of fee-for-service (FFS) payments for inpatient care ( 6 , 7 ), which has been associated with over-treatment and induced demand ( 8 , 9 ). In an effort to curb the increase of the health expenditure, many cities throughout China have tried to design and implement various case-based payment methods ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maryland's global hospital budgets also reduced the expenditure of medical care without having adverse impacts on hospital finances [34]. In 2016, a study in China investigated hospitals with different payment methods and found that the global budget can not only control the growth of medical care costs but also promote the improvement of medical quality [35]. Therefore, the global budget unified the interests of medical facilities, physicians, and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare expenditures tend to increase worldwide. The increase in healthcare spending has alarmed governments [ 1 , 2 ]. To control healthcare costs, policymakers are gradually replacing post-payment systems with anticipatory payment systems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%